The morphology and ecology of the genus synsepalum (A.Dc) Daniell (sapotaceae) in Nigeria (1999)
The genus Synsepalum is represented by three species in Nigeria. It is confined to the lowland rainforest region of the country. Synsepalum dulcificum is called the ‘miraculous’ berry or the 'magic plant' on account of the protein based sweetening agent miraculin found in the pulp of the fruit. The plant also produces a fairly hardwood which is particularly used as firewood by the indigenous people while the twigs are used as chewsticks. S. stipulatum popularly called the "Blacksmiths' charcoal wood" is known to supply the best charcoal to the Benin blacksmiths. S. glycydorum is not of much economic importance to the people but it is restricted in its distribution to the Southeastern part of Nigeria. From the standpoint of uses and restricted distribution, there is need for in-situ and ex-situ conservation of these species for sustainable utilization. The largest leaves with-the longest petioles are found in S. stipulatum, while the smallest leaves with the shortest petioles are in S. dulcifcum. The leaves and petioles of S. glycydorum are intermediate of the other two species. The leaves generally are elliptic to oblong to oblanceolate in shape with acuminate apices. However, the apex in S. dulcificum may be acute, rounded or rarely refuse. The leaf bases in the genus are usually cuneate. The leaves are glabrous except in S. dulcificum which may be hairy on the abaxial surface.